KONTRIBUSI KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS SOSIAL KABUPATEN LAMPUNG TIMUR - Diky Angga Hendrawan; Immawan Azhar Ben Atasoge (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine the influence of leadership and organizational culture toward employees’ performance at the Lelang Klass II Office Reza Berawi City of Bandar Lampung. The type of research used in this study is the Explanatory research model. The research method used is quantitative. This study used 20 research respondents. There are three variables in this study, namely: 2 (two) Independent variables (X1 and X2) and 1 (one) dependent variable where leadership (X1) and organizational culture (X2) as independent variables and employee performance (Y) as the dependent variable. Hypotheses test result showed that there is the influence of leadership (X1) toward employee performance (Y), with the level of influence of 44.6%. There is an influence of organizational culture (X2) toward employee performance (Y) with an influence level of 33.9%. There is the influence of leadership (X1) and organizational culture (X2) together toward employee performance (Y), with a degree of influence of 53.3%.